ELECTRO-DEGRADATIONOF REACTIVEBLUE DYES USINGCYLINDER MODIFIED ELECTRODE: Ti/&Beta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2010)
ABSTRACT A cylinder modified electrode of the I3-Pb02 was fabricated by anodic electro-deposition method on titanium substrate. The Pb02 layer prepared from high acid solution (pH: 0.3) that contains a mixed of 0.5 M Pb(N03J2,1 M HN03, and 0,02 M NaF. The physicochemical properties of the Pb02 electrode were analyzed by using Energy DispersiveX-Ray Analysis and X-Ray Diffraction. The analyses have shown that oxide layer has an O/Pb ratio about 1.6 and the PbO impurities are formed in the surface layer besides the I3-Pb02.The modified electrode was used as anode paired stainless cathode in the electro-degradation of reactive blue dye. The results of the electro-catalytic oxidation process of the dye solution were expressed in terms of the remaining intensity dye and chemical oxygen demand (COD) values. The modified electrode has removal efficiency of the reactive blue dye at voltage of 7 V,pH of 7, concentrationNaCI of 2 glL, initial dye concentrationof 100mglL with simple and short time operations.